vNOTES retroperitoneal sentinel lymph node dissection for endometrial cancer staging: First multicenter, prospective case series - Jan Baekelandt; Astrid Jespers; Daniela Huber; Levon Badiglian‐Filho; Andrea Stuart; Linus Chuang; Oudai Ali; Alexander Burnett (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction The current standard treatment for endometrial cancer is a laparoscopic hysterectomy with adnexectomies and bilateral sentinel node resection. A retroperitoneal vNOTES sentinel node resection has several theoretical potential advantages. These include being less invasive, leaving no visible scars, operating without Trendelenburg, and therefore offering the anesthetic advantage of easier ventilation in obese patients and following the natural lymph node trajectory from caudally to cranially and therefore a lower risk of missing the sentinel node. The aim of this study is to determine the feasibility of a retroperitoneal vNOTES approach to sentinel lymph node dissection for staging of endometrial cancer. Material and methods A prospective multicenter case series was performed in four hospitals. A total of 64 women with early‐stage endometrial carcinoma suitable for surgical staging with sentinel lymph node removal were operated via a transvaginal retroperitoneal vNOTES approach. The paravesical space was entered through a vaginal incision after injecting the cervix with indocyanine green. A vNOTES port was placed into this space and insufflation of the retroperitoneum was performed. Sentinel lymph nodes were identified bilaterally using near‐infrared light followed by endoscopic removal of these nodes. Results A total of 64 women with early‐stage endometrial cancer underwent sentinel lymph node removal by retroperitoneal vNOTES technique. All patients also underwent subsequent vNOTES hysterectomy and bilateral salpingo‐oophorectomy. The median age was 69.5 years, median total operative time was 126 min and the median estimated blood loss was 80 mL. In 97% of the cases bilateral sentinel nodes could be identified. A total of 60 patients had negative sentinel nodes, three had isolated tumor cells and one had macroscopically positive sentinel nodes. No complications with sequel occurred. Conclusions This prospective multicenter case series demonstrates the feasibility of the vNOTES approach for identifying and removing sentinel lymph nodes in women with endometrial carcinoma successfully and safely. vNOTES allows sole transvaginal access with exposure of the entire retroperitoneal space, following the natural lymph trajectory caudally to cranially, and without the need for a Trendelenburg position.